Challenges Faced by IIUM Postgraduate Students in Conducting the Qur’an Memorization and Working for Living During Their Study Period - M Husnaini; Noor Amili; Betania Kartika; Dawood Abdulmalek Yahya Al-Hidabi; Halim bin Ismail (International Journal of Asian Education, 2022)
This study looks at the difficulties that IIUM postgraduate students have when memorizing the Qur'an and working at the same time during their studies. The goal of this study is to find out how IIUM postgraduate students balanced Qur'an memorization and working activities during their studies, to identify the difficulties they faced, and to find out how they balanced Qur'an memorization and working activities. A case study was used in this study to create a qualitative design. The data was collected via methodical triangulation, and the data was gathered through verbal interviews. Two postgraduate students from IIUM were chosen to be interviewed. Thematic analysis was used to examine the data. The keywords were determined once the data from the interviews were transcribed. The researchers then identified the theme for further investigation before analyzing the data. The findings revealed that these students value Qur'an memorization but that there is no timetable for memorizing the whole Qur'an due to their busy schedules.